Educação Superior: um estudo sobre a ação docente dos (as) professores (as) do Centro de Educação da Universidade Federal da Paraíba a partir de suas representações sociais - Brito Filho, Galdino Toscano de (2007)
The present thesis has higher education as a central theme_ It is a study on the professors' action (performance) at the Education Center at Federal University of Paraiba, from their social representations viewpoint. It is a research developed at that Center and has the aim to analyse the professors' social representations on the importance of pedagogical formation for their teaching practice in higher education. A reflecting thinking was. made on the importance and the need for didatic-peciagogical formation, research and knowledge production as major conditions for a good performance of the professor in his/her daily classwork. By means of a qualitative research, and from analysis and discussion of the data gathered through questionnaires applied to 18 professors, one has confirmed the importance of creation a new knowledge acquirements in their formative processes. It was also found the type of perception the target-population members possess about themselves as teachers, and an emphasis was given to the relevant degree of pedagogical formations and knowledge in all teaching fields of higher education.